Rib stress fracture in a male adaptive rower from the arms and shoulders sport class: case report - Smoljanovic, T.; Bojanic, I.; Pollock, C. L.; Radonic, R. (Croatian Medical Journal, 2011)
Adaptive rowing is rowing or sculling for rowers with a physical disability. It debuted at the Paralympic Games in 2008. In order to ensure an equitable playing field, rowers with similar levels of physical function and disability are classified into different sport classes for competition. Rowers with an inability to use a sliding seat and impaired trunk function resulting in an inability to perform trunk forward and backward lean via hip flexion/extension are assigned to the Arms and Shoulders (AS) class. AS rowers have to use a chest strap set immediately below the chest in order to localize any trunk movement in AS class. Conditions created by adaptations of rowing equipment and technique within the AS class create unique stresses on the upper thoracic region. The following case report demonstrates how etiology and management of a rib stress fracture in an AS rower differs in comparison to able-body rowers. Of significant importance were the limitations imposed on the rower's ability to maintain rowing-specific fitness, due to the nature of the rib stress fracture and requirement to decrease force transmission through the ribs for several weeks. The rower's gradual return to full training was further impacted by obligatory use of the chest strap, which directly applied pressure over the injured area. Protective orthosis for the chest was designed and applied in order to dissipate pressure of the chest strap over the thorax during rowing (most importantly at the catch position) both on the ergometer and in the boat.